Adsorption of water and methanol on highly graphitized thermal carbon black: The effects of functional group and temperature on the isosteric heat at low loadings. (April 2016) - Klomkliang, Nikom; Kaewmanee, R.; Saimoey, S.; Intarayothya, S.; Do, D.D.; Nicholson, D.
Abstract: Isosteric heats of water and methanol adsorption on highly graphitized thermal carbon black have been studied using grand canonical Monte Carlo simulation to investigate the effects of the concentration of functional groups and temperature on the isosteric heats observed experimentally. The heat at zero loading is associated with the interaction between an adsorbate and the functional group. The variation in the heat with loading is due to a combination two effects: (1) Saturation of the functional groups by adsorbate molecules. (2) Adsorption at the convex boundary of the clusters, resulting in a lower number of neighbours for each new molecule adsorbed onto the clusters compared to the bulk liquid. The isosteric heat versus loading reaches a minimum and then increases again as the number of interactions with neighbouring molecules increases, and finally reaches the heat of liquefaction when the very large clusters approach liquid-like behaviour.